Anatomy of maxillary sinus and its ostium: A radiological study using computed tomography - Anne D Souza (CHRISMED Journal of Health and Research, 2016)
Background: Interventions involving the middle meatus are commonly performed because the majority of the paranasal sinuses open into the osteomeatal complex. Therefore, the aim of the present study was to locate the level of maxillary sinus ostium (MSO), to measure the distances between MSO and different anatomical landmarks, to measure the different dimensions of maxillary sinus and to compare the morphology of maxillary sinus between the right and the left sides. Materials and Methods: The study involved 50 computed tomography (CT) images of normal paranasal sinus anatomy in coronal and sagittal planes from the Department of Radiodiagnosis. The location of the sinus ostium (upper, middle, or lower third) was observed. Perpendicular distance from the sinus ostium to the lower border of inferior turbinate and hard palate were measured. The maximum vertical, transverse, and antero-posterior diameters of the maxillary sinus were measured. Results: Of 50 CT images, the MSO was located in the upper third in 40 cases while in 10 it was located in the middle third. The most common location of MSO was in the upper third. The dimensions of the maxillary sinus indicated bilateral symmetry. Conclusion: The dimensions of the maxillary sinus indicated bilateral symmetry, and there were no significant gender differences when compared. However, the distances of the MSO from the major anatomical landmarks were significantly different between males and females which are seldom reported earlier. This knowledge about the variations in the lateral wall of the nasal cavity is crucial during the endoscopic interventions and for functional endoscopic sinus surgeries.